Electrochemical and Electrocatalytic Properties of Cobalt Oxide Nanoparticles - EMAMALI SABZI, REZA; EBRAHIMZADEH, FATEMEH; SEDGHI, HASSAN (Asian Journal of Chemistry, 2010)
The synthesis and characterization of cobalt oxide nanoparticles are reported. Cobalt oxide nanoparticles prepared by two ways. In first way cobalt chloride mixed with sodium carbonate, the obtained precipitate react in solid state reaction with oxalic and citric acid separately at about 70 ºC, then products oxidized by heating at different temperature from 400-700 ºC. In second way the cobalt chloride mixed with sodium hydroxide solutionat at 4 ºC and obtained precipitate heated as the first way from 400-600 ºC. The obtained cobalt oxide nanoparticles characterized by cyclic voltammetry and SEM techniques. The electrochemical behaviour of the cobalt oxide in carbon paste electrode (CPE) was studied by cyclic voltammetry. The cobalt oxide-CPE shows a pair of peaks with a surface-confined characteristic in a 0.5 M phosphate buffer and 0.5 M NaOH as supporting electrolyte. The cobalt oxide-CPE showed electrocatalytic activity toward oxidation of fructose. The kinetics of the catalytic reaction was investigated by using chronoamperometry.